College admissions and the role of information: An experimental study - Pais, Filipa (2022)
Three well-known matching mechanisms designed to solve the college admissions problems are analyzed in the experimental laboratory in different informational settings.We observe that when the level of information is significantly increased, the proportion of schools and teachers that submit their true preferences decreases. This affects largely the efficiency and stability of the Gale–Shapley and the Boston mechanisms. The TTC mechanism is less sensitive to information and outperforms the other two mechanisms in terms of efficiency and stability, and it is as successful as them in extracting private information.